The Role of School Leadership in Enhancing Teacher Work Discipline - Dermawan, Oki; Yusnita, Erni; Putri, Adinda (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2026)
Effective school leadership is central to the development of teacher professionalism and organizational discipline, yet qualitative evidence from Islamic secondary schools remains limited. This study investigated how school leadership strengthened teacher work discipline at MTs Negeri 2 Pesawaran, Indonesia. The study used a qualitative descriptive field design and drew on semi-structured interviews, non-participant observation, and document analysis. The revised manuscript reports a purposive sample consisting of the madrasah head, the vice principal for curriculum, and teachers who were directly involved in daily instructional management. Data were analyzed using the Miles, Huberman, and Saldaña interactive model through data reduction, data display, and conclusion drawing, with credibility supported by source and technique triangulation. The findings converged on three interrelated leadership pathways. First, the madrasah head directed teachers through clear attendance regulations, supervisory routines, duty allocation, and regular coordination meetings. Second, leadership was enacted through mentoring practices, including evaluation meetings, performance agreements, professional guidance, and collaborative problem solving. Third, the madrasah head functioned as an exemplary role model by demonstrating punctuality, open communication, recognition of teacher achievements, and active participation in school programs. Collectively, these practices strengthened punctuality, accountability, professional commitment, and a collaborative school culture. The study suggests that leadership in madrasah settings is most effective when administrative control is combined with ethical example, participatory communication, and sustained professional support. These findings contribute context-specific insight into how leadership mechanisms shape work discipline in Islamic educational institutions and provide practical direction for school leaders seeking to reinforce teacher accountability in comparable settings.